2005
DOI: 10.1081/cus-200059587
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Skin Irritation Potential of Facial Tissues

Abstract: This assay detects significant panelists' preferences and, therefore, forms a useful part of the arsenal for evaluating skin effects and claims support. However, without further modification, the assay is not sufficiently robust to reliably detect differences in the clinical measures of irritant effects (erythema and dryness).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…In addition, panelists were also interviewed about specific aspects of product preferences. Statistical analysis revealed that the panelists' subjective product preferences were more consistent in distinguishing between the test product than were either erythema or dryness (92).…”
Section: Exaggeration Of Test Conditionsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, panelists were also interviewed about specific aspects of product preferences. Statistical analysis revealed that the panelists' subjective product preferences were more consistent in distinguishing between the test product than were either erythema or dryness (92).…”
Section: Exaggeration Of Test Conditionsmentioning
confidence: 97%
“…Irritant reactions to feminine-care products have been reported (81) with a few feminine products that contain chemicals known to be irritants in certain doses (92). However, the potential for heightened vulvar susceptibility to topical agents is not widely reported in literature (22).…”
Section: Anatomic Sitementioning
confidence: 98%
“…Nevertheless, consumers develop product preferences on the basis of perceived skin effects that are not always predictable based on results of the skin effect testing programs such as the ones described above. Sensory data collected from panelists participating in skin effect testing indicate that panelists can sometimes discriminate between products on the basis of how they feel during use, even when clinically evaluated skin effects (erythema and dryness) show no differences [36][37][38]. Additionally, an important subgroup of consumers for products intended for the genital area is constituted by the elderly.…”
Section: Future Challengesmentioning
confidence: 96%
“…Sensory data are collected using simple questionnaires to determine the frequency of unpleasant sensations such as dryness, burning and itching. We have incorporated measures of sensory effects in clinical studies on feminine hygiene pads and wipes [33,45,46], nasal irritation studies [37] and BTK studies [36].…”
Section: Add Additional Endpointsmentioning
confidence: 99%
See 1 more Smart Citation